Analysis of Foveal Avascular Zone for Grading of Diabetic Retinopathy - Ahmad Fadzil, M Hani; Izhar, Lila Iznita; Nugroho, Hanung Adi (Inderscience Publishers, 2011)
At present, it is difficult to determine foveal avascular zone (FAZ) enlargement based on colour fundus images. Fundus image analysis presents several challenges such as high image variability, improper illumination and artifacts. A new approach for grading diabetic retinopathy (DR) by analyzing FAZ enlargement in colour fundus image has been developed. Investigations show that FAZ area ranges can be used to indicate progression of the disease. The mean accuracy and standard deviation of ranges obtained are 92.2% and 3.22, respectively. This new approach is reliable, accurate and fast compared to the current method based on DR pathologies